Benefits and Drawbacks of Using Hotels as Shelters After a Landslide. (10th October 2022) - Tada, Shinya; Jitsuiki, Kei; Ohsaka, Hiromichi; Yanagawa, Youichi
Abstract: Objectives: On July 3, 2021, a landslide occurred in part of Atami City, Shizuoka, Japan. Methods: The government of Shizuoka Prefecture requested the dispatch of Shizuoka Disaster Medical Assistance Teams (S-DMATs). Results: On day 2, the evacuees were evacuated into 2 hotels (A and B). Hotel A accommodated over 570 independent and dependent evacuees. Hotel B accommodated 44 dependent aged individuals, who lived in the same long-term health-care facility, together with their 11 caregivers. The evacuees in hotel B returned to the previous facility on day 10 without any specific medical problems. The evacuees in hotel A were managed in the guest rooms as family units. Individuals requiring care in guest rooms in hotel A became isolated because they could not call for help or walk. Furthermore, hotel guest rooms were not barrier-free. The S-DMATs supported the evacuees. Conclusions: Independent evacuees received the maximum benefits from the use of a hotel as a shelter. In contrast, it was difficult for dependent evacuees to benefit from the hotel as it is as a shelter when living alone in the hotel. Dependent evacuees required appropriate support to eat, walk, use the toilet, and keep themselves clean when using a hotel as a shelter.